2015
DOI: 10.1021/acs.jced.5b00322
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibria of CO2 and CH4 Hydrates in Intergranular Meso/Macro Pores of MIL-53 Metal Organic Framework

Abstract: The formation of gas hydrates in porous media is expected to bring out beneficial properties for gas storage and separation. Appropriate combined use of both gas hydrate and highly porous metal organic frameworks (MOFs) can be useful for achieving advances in the field of gas storage and separation. This makes understanding the behavior of gas hydrates in the confining pores of MOF crucial. The formation and phase equilibria of CO 2 and CH 4 hydrates in MOF were investigated using MIL-53 MOF through low-temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 48 publications
(86 reference statements)
3
44
0
Order By: Relevance
“…the dissociation in the confined nanospace is slightly promoted compared to the bulk system. This observation can be attributed to the geometric change of water activity in the confined nanospace as described by Handa et al 10 A similar behaviour was observed for gas hydrates confined in metal-organic-framework MIL-53(Al) 26 and porous glasses. 27…”
Section: Phase Diagrams Of Methane Hydrate Formation In Confined Spacesupporting
confidence: 72%
“…the dissociation in the confined nanospace is slightly promoted compared to the bulk system. This observation can be attributed to the geometric change of water activity in the confined nanospace as described by Handa et al 10 A similar behaviour was observed for gas hydrates confined in metal-organic-framework MIL-53(Al) 26 and porous glasses. 27…”
Section: Phase Diagrams Of Methane Hydrate Formation In Confined Spacesupporting
confidence: 72%
“…Although the difference in dissociation temperature (system without zeolite versus system with zeolite) is nearly commensurate with the precision of the HP-DSC (±0.5 °C), the trend is distinct for each zeolite with small deviations. Studies in the literature found that a decrease in hydrate dissociation temperature correlates to thermodynamic inhibition, which can be caused by hydrates forming in a confined space, such as the interparticle spacing, restricting the water activity and in consequence shifting the phase envelope. , To reiterate, the pores of both zeolites in this study (∼0.74 nm, shown in nitrogen adsorption isotherms at 77 K in Figure S5) are too small for hydrate formation (structure I unit cell size 1.2 nm) to take place within the pores; thus, the formation is most likely taking place in the interparticle spacing.…”
mentioning
confidence: 55%
“…Kim et al. evaluated the methane hydrate formation in metal organic framework MIL‐53 . Despite the presence of microporosity, methane hydrates could only form in meso‐ and macropores due to steric restrictions (MIL‐53 pores are ≈0.6 nm while sI hydrate lattice is ≈1.2 nm).…”
Section: Methane Hydrate In Confined Spacesmentioning
confidence: 99%